I feel machine - Able, Krent; Hanshaw, Julian 1971-; Svetoft, Erik 1988-; Brown, Box 1980-; Tan, Shaun 1974-; Walden, Tillie 1996- (SelfMadeHero, 2018)
Uploading -- Sthlmtransfer -- Here I am -- Contours -- Be little with me -- Bloody kids
Keywords: Able, Krent; Brown, Box -- 1980-; Hanshaw, Julian -- 1971-; Tan, Shaun -- 1974-; Walden, Tillie -- 1996-; Svetoft, Erik -- 1988-; Technik; Motiv; Mensch; Technology / Social aspects / Comic books, strips, etc; Technology; Social aspects; Comic books, strips, etc; Comics (Graphic works); Graphic novels; Fiction; Comic